Primary hepatic adenosquamous carcinoma: a case report and review of the literature - Ai, Haidong; Gong, Ting; Ma, Yongbiao; Ma, Guixu; Zhao, Jingjing; Zhao, Xuelin (Frontiers in Oncology, 2023)
Primary hepatic adenosquamous carcinoma is considered a rare subtype of intrahepatic cholangiocarcinoma, with fewer than 100 domestic and international cases reported. This malignancy exhibits a high degree of malignancy, strong invasiveness, and an unfavorable prognosis due to its propensity for early lymph node and intrahepatic metastasis. The etiology of this disease remains uncertain, and preoperative diagnosis is exceedingly challenging owing to the nonspecific clinical features and lack of specificity in imaging studies. Radical surgical resection is the most effective treatment for non-metastatic tumors, while targeted adjuvant therapy administered postoperatively can enhance therapeutic efficacy and delay tumor recurrence. This article documents the diagnostic and therapeutic course of a case of primary hepatic adenosquamous carcinoma treated at our medical institution, along with a comprehensive synthesis of the clinical characteristics and advances in the diagnosis and treatment of this disease, aiming to augment understanding and serve as a reference for future clinical endeavors.